Australian Wild Rice Populations: A Key Resource for Global Food Security - Henry, Robert J. (Frontiers in Plant Science, 2019)
Rice is one of the most important food crops contributing to the diet of large numbers of people especially in Asia. Rice (Oryza sativa) was domesticated in Asia many thousands of years ago and more recently independently in Africa. Wild rice populations are found around the tropical world. The extensive production of rice in many areas has displaced the wild populations that were the basis of the original domestications by humans. Recent research, reviewed here, has identified wild rice species in northern Australia that have been isolated from the impact of domestication in Asia. Wild rice populations contain novel alleles that are a source of desirable traits such as erect habit, disease resistance, large grain size, and unique starch properties. These populations include the most diverse genotypes within the primary gene pool of rice and more distant wild relatives. Genome sequencing also suggests the presence of populations that are close relatives of domesticated rice. Hybrid populations that demonstrate mechanisms of ongoing evolution of wild Oryza have been identified in the wild. These populations provide options for both new domestications and utilization of novel alleles to improve or adapt domesticated rice using conventional or preferably new breeding technologies. Climate change and growing food demands associated with population and economic growth are major challenges for agriculture including rice production. The availability of diverse genetic resources to support crop adaptation and new crop domestication is critical to continued production and increased efforts to support in situ and ex situ conservation of wild Oryza and related species are warranted.